2021
DOI: 10.1051/mfreview/2020039
|View full text |Cite
|
Sign up to set email alerts
|

Experimental analysis of process parameters in drilling nimonic C263 alloy under nano fluid mixed MQL environment

Abstract: Nimonic C263 is a super alloy and it is difficult to cut. As this alloy possess high proportion of chromium, cobalt, and molybdenum, which fortify the material by solution hardening, which inhibits the dislocation movement, resulting in higher plastic deformation. In this research, an attempt has been made to model, analysis and investigate the machining characteristics such as thrust force, temperature at drill cutting edge, flank wear and surface finish during drilling of this alloy using silver nano fluid m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…The authors concluded that the FR followed by the CS, the concentration of nanoparticles, and the coolant pressure was the order of importance in deciding the tool wear. It was also reported that the temperature and the SR increased with a lower coolant pressure and nanoparticle concentration [87]. Nagaraj et al [88] developed a FEMbased simulation model to predict the force and temperature generated during the drilling of Nimonic C263 using a coated carbide drill bit.…”
Section: Drillingmentioning
confidence: 99%
“…The authors concluded that the FR followed by the CS, the concentration of nanoparticles, and the coolant pressure was the order of importance in deciding the tool wear. It was also reported that the temperature and the SR increased with a lower coolant pressure and nanoparticle concentration [87]. Nagaraj et al [88] developed a FEMbased simulation model to predict the force and temperature generated during the drilling of Nimonic C263 using a coated carbide drill bit.…”
Section: Drillingmentioning
confidence: 99%
“…As discussed previously, the MQL technique is often used to minimise the use of cutting fluids [79,80]. In one research work, the turning operation was conducted on Titanium alloy using a polycrystalline diamond tool to optimise various parameters resulting in a decrease in R a [81].…”
mentioning
confidence: 99%